2009
DOI: 10.1136/jcp.2009.065219
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of sentinel lymph nodes with metastatic breast cancer indicates three distinct patterns of tumour growth

Abstract: This methodology provides improved understanding of metastatic disease development and potentially could be used to develop strategies to improve techniques for its routine detection. Further studies are required in order to evaluate the prognostic and biological significance of the growth patterns identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…In a previous proof-of-principle study,35 we demonstrated that metastatic growth in ALN occurs in three distinct patterns: sinusoidal, nodular and diffuse. The preliminary results suggest that metastatic patterns may have prognostic significance with the sinusoidal pattern being related to a poor prognosis and the diffuse pattern with a good prognosis.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a previous proof-of-principle study,35 we demonstrated that metastatic growth in ALN occurs in three distinct patterns: sinusoidal, nodular and diffuse. The preliminary results suggest that metastatic patterns may have prognostic significance with the sinusoidal pattern being related to a poor prognosis and the diffuse pattern with a good prognosis.…”
Section: Introductionmentioning
confidence: 63%
“…Three different growth patterns were noted within the LNs; sinusoidal, where the tumour cells were present within the subcapsular sinus of the ALN; nodular, where the tumour cells formed a clump, or nodule, of tightly packed cells in the cortex and and/or medulla of the node; and diffuse, where the tumour cells were dispersed through the cortex and/or medulla of the node in a diffuse spreading pattern. In some sections, only one growth pattern was seen, whereas in others they were seen in combination 35. If a pattern combination was present, the predominant pattern was noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early 3D reconstructions using serial sections involved a laborious process involving taking camera lucida pictures of sections, cutting and stacking the resulting plates, and building a 3D model of the underlying structure [5]. With the development of new technologies, it is now possible to combine high resolution serial sections in silico to create a 3D image of breast cancer [6][7]. For example, in [6], the authors mapped invasive breast cancer in a 1x1x1 cm tissue sample and built a 3D representation.…”
mentioning
confidence: 98%
“…For example, in [6], the authors mapped invasive breast cancer in a 1x1x1 cm tissue sample and built a 3D representation. The spread of metastatic growth could also be visualized from 3D reconstructions of sentinel lymph nodes [7]. Another germane investigation examined the 3D ductal structure of a normal breast [8] and determined the branching and independence of the ducts, including some with DCIS.…”
mentioning
confidence: 99%